Biofunctional electrospun nanofibrous scaffolds in tissue engineering and the potential application of siRNA-delivery for nerve regeneration - Cao, Haoqing (2011)
The application of tissue engineering has been extensively explored for decades to improve biological functions. New strategies and technologies have been continuously developed in various fields over time. Among these developments, the use of tissue engineering scaffolds for nerve regeneration has important implications in understanding neural cell biology and recovering nerve functions. In this thesis, the potential application of electrospun nanofibrous scaffolds endowed with chemical and topographical signals for nerve regeneration was investigated. The versatility of electrospinning technique was first explored by producing diverse and functional fibrous scaffolds using biocompatible polymer polycaprolactone (PCL). Fiber properties can be tailored for specific purposes by altering operational parameters during electrospinning process and/or modification of poly properties. Core-shell structured fibers were introduced by co-axial electrospinning method, where scaffolds can be functionalized with desired characteristics. A scaffold-based drug delivery system was developed by incorporating small interfering RNA (siRNA) into PCL nanofibers for long-term RNA interference (RNAi) therapy. Intact siRNA was gradually released from nanofibers in a sustained manner for at least 49 days under physiological conditions. Compared to conventional bolus delivery, the scaffold-medicated delivery system is able to enhance cellular uptake and may decrease non- specific targeting to adjacent cells when applied in vivo. Meanwhile, topographical cues presented by the electrospun fibers also have profound impact on modulating cellular behaviors such as attachment, proliferation and differentiation. Therefore, nanofiber topographical effects on astrocyte phenotypic changes, including the uptake of siRNA and the corresponding gene-silencing efficiency, were investigated to gain insights to construct a novel scaffold to deliver siRNA for CNS regeneration. Suppressed astrocytic growth, elevated apoptosis and enhanced gene silencing efficiency were observed on nanofibers in comparison with two-dimensional flat surfaces. These results suggested that the electrospun nanofibrous scaffolds may serve as a potential therapeutic treatment for nerve regeneration. We also investigated the biocompatibility with regard to scaffold architecture and topographical effect of nanofibrous scaffolds on the in vivo and in vitro foreign body reaction. PCL electrospun nanofibers with random and aligned fiber orientations yielded significantly thinner fibrous capsules compared to solid surfaces when implanted subcutaneously in rat. Furthermore, cell infiltration and cell-scaffold interaction were observed on the aligned fibrous scaffolds. Altogether, these results demonstrated the potential application of the bio-functionalized electrospun nanofibers for general tissue engineering applications and neural regenerative medicine.